Letter : Ray Cox Memorial - Witt, L.
042-0105-001 THE JOINT COUNCIL of the SOUTHAMPTON TRADES COUNCIL, LABOUR PARTY and CO-OPERATIVE SOCIETY PROSPECT HOUSE, 160 ABOVE BAR, SOUTHAMPTON Hon. Secretary : Mr. L. WITT Telephone : 5191 Southampton Trades Council Hon. Secretary : Mr. R. Chick 107 Earls Road Southampton Labour Party Secretary and Agent : Mr. A. Rose 54 Henstead Road Telephone : 2427 Southampton Co-operative Society, Ltd. (Development Committee) Secretary : Mr. L. Witt, Prospect House 160 Above Bar Telephone : 5191 4th October, 1937. Sir Walter Citrine, K.B.E., Secretary, National Council of Labour, Transport House, Smith Square, London, S.W.1. Dear Sir, RAY COX MEMORIAL. I beg to refer to your letter of 3rd August (Ref:- WMC/WJB/AC/934) in reply to my enquiry of the 31st July, with reference to the photograph of the Anaesthetic apparatus purchased for the Ray Cox Memorial. I shall be glad to know if Mr. Schevenels has yet been able to let you have a copy of the photograph. Yours truly, L. Witt Hon.Sec. 292/946/42/105